THE EFFECT OF BLENDED LEARNING METHODS DURING THE COVID 19 PANDEMIC ON STUDENTS OFTHE HOSPITALIZATION STUDY PROGRAM - Wiyanti, Wiyanti; Anggraini, Puput Dewi (Journal of Indonesian Tourism and Policy Studies, 2021)
The COVID-19 pandemic has impacted all sectors including the education sector, forcing the face-to-face learning process to switch to online learning. There are many obstacles when conducting online learning in vocational education, especially hospitality study programs, including during practical courses. In situations and conditions like this, the blended learning model is deemed appropriate and can be used as an alternative learning model that is able to combine online and face-to-face learning processes. This study intends to analyze the effect of the teaching and learning process through the blended learning model in increasing the learning independence of students in the hospitality study program at Harapan Bersama Tegal Polytechnic. This research is expected to be able to encourage students to follow the blended learning learning process properly so that there is an increase in learning independence. This research is a quantitative research with a survey design. The research will be conducted at the Harapan Bersama Tegal Polytechnic with the research subjects, namely students of the hospitality study program at the Harapan Bersama Tegal Polytechnic, totaling 69 students. Analysis of the data used to answer the research problem is to use regression analysis. This research has succeeded in proving that there is a positive and significant effect of blended learning on the learning independence of students of the Hospitality Study Program at the Harapan Bersama Polytechnic, Tegal.